Comparative study of enzyme dehydrogenase activity in Cicer arietinum and Arachis hypogea - Jain, Praveen; Bharadwaj, Meenakshi; Bakshi, Jyoti (Recent Research in Science and Technology, 2013)
Viability of seeds can be determined by the dehydrogenase activity of the constituent cells. Enzyme activity can be seen both inside and outside the cell. Dehydrogenase activity can be observed by the formation of formazan compound, a red dye, from 2, 3, 5, Triphenyl Tetrazolium Chloride (TTC). Dehydrogenase can catalyze the reaction. Initially red colour is observed in the seed tissues and gradually the whole solution turns red. Change in colour of the solution is observed with respect to time. A comparative study is conducted between Cicer arietinum(chick pea) and Arachis hypogea( ground nut). Higher enzyme content is reported in chickpea as the reaction is completed in 18 hours, as compared to groundnut where the reaction takes 48 hours to complete. It is seen that the content of enzyme and rapid leaching of formazan is responsible for the process.